DAYA SAING USAHATANI KEDELAI DI DESA WONOKALANG KABUPATEN SIDOARJO - Eko Nurhadi (University of Jember, 2009)
Soybean is strategic commodities in Indonesia. Therefore, efforts to soybean sufficiently not only aim to fulfill food need, but also to support agroindustry and save foreign exchange with decrease dependence towards import foodstuff. But, potential big market and then bloom not yet can be maked use in an optimal with domestic product development such as technical problem, social, and economy. When does economy social condition condusif so technically has potential and opportunity good, because farmer decision participates in soybean product increase economy climate that beneficial and also according to social acceptable.The aims are (1) Analyze influential factor towards production usahatani soy bean at Wonokalang Village, Wonoayu District, Sidoarjo Regency. (2) Analyze competitive superiority usahatani soy bean at Wonokalang Village, Wonoayu District, Sidoarjo Regency. Population in this research is as much as 140 farmer respondents and sample as much as 30 soybean farmers uses method purposive random sampling with criteria faemwr who owner the tune status, penyakap and tenant. Analysis method that used to measures system competitive superiority soy bean farming Private Cost Ratio (PCR) and Cobb - Douglas. PCR and Cobb - Douglas can give analysis sketch enough comprehensive hit competitive superiority, towards every agriculture commodities that be more importanter to see is production commodities in country compete in global market.The result shows that factor - factors of production that is land, seed, chemistry fertilizer, organic fertilizer, insecticide and labour positive influential with variable influence level as a whole as big as 98,5% and 1,5% influenced by variable other not at pack into this discussion. Product value marginal (NPMXI/ Pxi) in soy bean farmingat Wonokalang Village, Wonoayu District, Sidoarjo Regency< 1 mean factors of production use not yet efficient economically that is vast tune, seed, chemistry fertilizer, organic fertilizer, insecticide and labour besides, got result that usahatani soy bean at Wonokalang Village, Wonoayu District, Sidoarjo Regency has competitive superiority, at show coefficient value privat cost ratio (pcr) that is 0,584.Keyword: Competitiveness, soybean and policy.